Bortezomib for the Treatment of Hematologic Malignancies: 15 Years Later - Pawel Robak; Tadeusz Robak (Adis, Springer Healthcare, 2019)
Abstract Bortezomib is a dipeptidyl boronic acid that selectively inhibits the ubiquitin proteasome pathway, which plays a role in the degradation of many intracellular proteins. It is the first-in-class selective and reversible inhibitor of the 26S proteasome, with antiproliferative and antitumor activity. It exerts its anti-neoplastic action mainly via the inhibition of the nuclear factor-κB pathway components associated with cell proliferation, apoptosis, and angiogenesis. The drug has revolutionized the treatment of multiple myeloma and, more recently, mantle cell lymphoma. In 2003, bortezomib received accelerated approval from the US Food and Drug Administration for the treatment of relapsed/refractory multiple myeloma and in 2008 for patients with previously untreated multiple myeloma. In 2006, bortezomib was approved for the treatment of refractory/relapsed mantle cell lymphoma and, in 2014, for previously untreated mantle cell lymphoma. Bortezomib has also demonstrated clinical efficacy both as a single drug and in combination with other agents in light chain amyloidosis, lymphoplasmacytic lymphoma/Waldenstrom macroglobulinemia, and peripheral T-cell lymphomas. Furthermore, continued clinical studies are required to confirm its value for patients with indolent and aggressive B-cell non-Hodgkin lymphomas and acute leukemias.